Medicine and Media: The Ranitidine Debate - Jennifer A. Wagner; Jennifer M. Colombo (Wiley, 2020)
Ranitidine has been the topic of recent media reports. Current findings, confirmed by the US Food and Drug Administration, indicate that some ranitidine products contain a substance that may be carcinogenic. Providers and patients require additional information on the risks of continuing therapy vs. the benefits of the medication. This article comments on what is currently known about the evolving situation of elevated N‐nitrosodimethylamine levels in ranitidine and the limits of the existing information to assess best practices.